Remotely Sensed Chlorophyll-A Variability in the Straits of Malacca - Ali Yousif, Abdel Galeel (2009)

(untitled)
Studies on the marine plankton in Malaysian waters are limited, and most of the studies have been mainly taxonomic and qualitative in nature. The present study investigates the spatial and temporal distribution of SeaWiFS derived-chlorophyll-a in the Straits of Malacca. A period of six consecutive years from 1998 to 2003 is studied. Validation of in situ chlorophyll-a measurements with their corresponding SeaWiFS chlorophyll-a data is carried out. The correlation of sea surface temperature (SST) with the temporal chlorophyll-a data is investigated. The relationship between the Southern Oscillation Index (SOI) values and chlorophyll-a data is discussed. Finally, the correlation of marine fish landings with chlorophyll-a data is revealed. SeaWiFS Data Analysis System (SeaDAS) has been used in SeaWiFS chlorophyll-a data analysis. In its typical use for the study of chlorophyll-a variability in tropical cloudy areas, ocean colour imagery is often binned in space and time. Comparison of in situ and SeaWiFS derived chlorophyll-a reveals that there is a moderate, positive correlation (r = 0.51) between the in situ and SeaWiFS chlorophyll-a observations, and the correlation is significant (P <0.05) at the 0.05 level. With the six years of nearly continuous monthly images from the SeaWiFS instrument, the patterns of chlorophyll-a variability at Straits of Malacca have thus been investigated. The results show spatial variability of chlorophyll-a in the Straits of Malacca. High chlorophyll-a concentration value (4.42 mg m-3) has been observed along the near coastal area. Chlorophyll-a value (0.39 mg m-3) decreased towards the offshore areas. Chlorophyll-a distribution was higher in the central (2.68 mg m-3) and southern parts (3.80 mg m-3) of the Straits of Malacca compared to the northern parts (1.16 mg m-3). The results also show seasonality of chlorophyll-a and SST variations in the Straits of Malacca. Phytoplankton bloom events were also revealed during the northeast monsoon season all over the Straits of Malacca. The peak concentrations of chlorophyll-a were prevailed during the northeast monsoon months (2.73 mg m-3). Chlorophyll-a concentration is relatively low during the southwest monsoon (1.68 mg m-3) and the two inter-monsoons months and was confined to the coastal areas. SST is low during the northeast monsoon months (28.31oC) and high during the southwest monsoon (30.32oC) and the two inter-monsoon months. A negative correlation was observed between the temporal SST and chlorophyll-a. Strong negative SOI value (-28.5) occurred in 1998 and was associated with low chlorophyll-a values. Positive SOI values observed in 1999 were associated with high chlorophyll-a values. It was found that the monthly marine fish landings value (39,391 metric tonnes) during the northeast monsoon months is lower than the monthly marine fish landings value (45,637 metric tonnes) during the southwest monsoon months. The research has demonstrated that satellite remote sensing is capable of identifying, quantifying and mapping chlorophyll-a in the study area. The variability between SeaWiFS and in situ chlorophyll-a data explains the typical nature of Case II waters. The spatial chlorophyll-a distribution is associated with hydrographic features of the Straits of Malacca, and the temporal variation of chlorophyll-a concentrations is related to temporal variations in SST distributions and availability of nutrients. Strong relationships exist between ocean colour and other physical parameters such as SST. The negative correlations between chlorophyll-a and fish production with the SOI are attributed to the negative effects of the El Niño in the study area